2015
DOI: 10.1007/s13277-015-3400-8
|View full text |Cite
|
Sign up to set email alerts
|

miR-30 overexpression promotes glioma stem cells by regulating Jak/STAT3 signaling pathway

Abstract: Malignant glioma is the most common intracranial tumor with poor prognosis. It is well believed that glioma stem cells (GSCs) are responsible for the initiation and progression of glioma. Janus kinase/signal transducer and activator of transcription (Jak/STAT3) pathway plays a key role in the functions of GSCs. However, the regulatory mechanism of Jak/STAT3 pathway has not been completely elucidated. This study employed multidisciplinary approaches to investigate the upstream regulators of Jak/STAT3 signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…Zhao et al [26] found that miR-30a functions as a tumor suppressor by targeting the oncogenic Wnt/beta-catenin/BCL9 pathway in H929 cells. Che et al [27] found that miR-30 overexpression promoted glioma stem cells by regulating the Jak/STAT3 signaling pathway. miR-30a activity was also found to be regulated by competitive endogenous RNA (ceRNA).…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [26] found that miR-30a functions as a tumor suppressor by targeting the oncogenic Wnt/beta-catenin/BCL9 pathway in H929 cells. Che et al [27] found that miR-30 overexpression promoted glioma stem cells by regulating the Jak/STAT3 signaling pathway. miR-30a activity was also found to be regulated by competitive endogenous RNA (ceRNA).…”
Section: Discussionmentioning
confidence: 99%
“…322 MiR-30 targets SOCS3 in glioma stem cells. 337 Mir-93 downregulates the expression of JAK1 and STAT3 to induce the differentiation of breast CSCs. Mir-218 negatively regulates the IL-6 receptor and JAK3 gene expression in lung CSCs.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%
“…Previous studies have highlighted the importance of miR-30 in the development and progression of cancer (20)(21)(22)(23). It has previously been demonstrated that miR-30 is associated with inflammatory responses (24-26).…”
Section: Discussionmentioning
confidence: 99%